2008
DOI: 10.4103/0972-0707.43413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of natural smile: Golden proportion, RED or Golden percentage

Abstract: Creating geometric or mathematical proportion to relate the successive width of maxillary anterior teeth is a critical aspect in Esthetic dentistry. Golden proportion, recurring esthetic dental (RED) proportion and golden percentage are new theories in this field.Aim:To investigate the existence and suitability of Golden proportion, Recurring Esthetic Dental, and Golden percentage between the widths of maxillary anterior teeth in individuals with natural dentition, with the aid of digital photographs and compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 8 publications
6
30
1
Order By: Relevance
“…The results for Malaysian population were comparable to the results reported in similar studies of other populations, including Turkish [1], Iranians [5,18], Jordanians [13], Americans [16], Indians [19] and Caucasians [20]. …”
Section: Discussionsupporting
confidence: 84%
“…The results for Malaysian population were comparable to the results reported in similar studies of other populations, including Turkish [1], Iranians [5,18], Jordanians [13], Americans [16], Indians [19] and Caucasians [20]. …”
Section: Discussionsupporting
confidence: 84%
“…The lack of Divine Proportion among dental and facial structures are also stated in recent literature attesting this proportion as an unsuitable method to relate dentofacial dimensions with natural or even “attractive” appearance during rehabilitation treatments. [ 23 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, golden proportion existed only in 14 to 25% of dental students of Asian origin. 8 However, Kanaparthy et al found that R2 in male and R1 in female correspond to the golden ratio whereas R1 in male and R2 in female do not. 10 Golden proportion was found only in R1 in 17% of samples from University of North Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] This ratio has been found to vary with race, gender, and ethnicity. [8][9][10] In considering the factors affecting this perceived esthetic ratio, the vertical dimension of the face and malocclusion type has been given less importance. Hence, this study was carried out with the aim of assessing the apparent tooth to tooth proportion of maxillary anterior region and finding out the possible association with lower anterior facial height and malocclusion type.…”
Section: Introductionmentioning
confidence: 99%